The Relationship between the Role of Health Workers and Community Leaders with the Occurrence of Dengue Hemorrhagic Fever - Tesha Pertiwi; Nurmaini; Etti Sudaryati (Britain International for Academic Research (BIAR) Publisher, 2020)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus that attacks the human body. One factor that can be overcome by counseling to the community by health workers and community leaders. In 2018, Medan experienced an increase in DHF cases, that is as many as 1490 cases, and the death rate due to DHF was 13 people, this condition is still a health problem that must be dealt with immediately. This study aims to analyze the relationship between the health workers and community leaders with the occurrence of DHF. This type of research is descriptive, with cross-sectional design. The study population are all families in Medan, the study sample as many as 300 families which taken by using simple random sampling technique. The data collection tool uses a questionnaire. The results showed that the level of health workers in the prevention of DHF was in good criteria only 7.7 percent and the level of support of community leaders in preventing DHF was in good criteria only 9.7 percent. Bivariate analysis shows that there was no significant relationship between the health workers and community leaders with the occurrence of DHF in Medan. The role of health workers and community leaders was still lacking in efforts to prevent DHF. It is recommended that health workers and community leaders play an active role in providing counseling to the public about DHF.